Using Diffused Essential Oils to Remove Airborne Pine and Pecan Pollen: A Pilot Study - James T. Davis; Kyle Lorenzen; Ariel Poulson; Richard E. Carlson (Applied Sciences, 2022)
Pollen is a major source of allergies, and its prevalence is rising. Essential oils, primarily composed of terpenes, are easy to diffuse and are becoming more common to use in the home. To test the effect of diffusing essential oils on indoor pollen, pollen was introduced into an enclosed environment containing an ultrasonic diffuser. Lavender, Citrus Fresh™, and Thieves® were tested against lodgepole pine pollen. Lavender was also tested against pecan pollen. An ultrasonic diffuser, containing either 100 mL of reverse osmosis (RO) water or 100 mL of RO water and 10 drops of an essential oil, was diffused in the environment to see how they would influence the amount of pollen that was deposited on the collection slides, compared to when the diffuser was off. The results show that diffusing RO water and lavender, Citrus Fresh™, or Thieves® essential oil increased the amount of lodgepole pine pollen deposited on the floor of an enclosed environment. Diffusing either RO water alone or RO water and lavender essential oil increased the amount of pecan pollen found on the floor of an enclosed environment. This suggests that a diffuser may help remove pollen from the air and potentially aid in alleviating allergies.